A Novel Process for Synthesis of Iron-Alumina Spinel and Its Application in Refractory for Cement Rotary Kiln. Issue 3 (3rd July 2017) - Padhi, L. N.; Sahu, P.; Sahoo, N.; Singh, S. K.; Tripathy, J. K.
ABSTRACT: Historically chromite was used as a component in magnesia chrome refractory due to its high flexible character (low modulus of elasticity). But use of magnesia chrome bricks in the sintering zone of cement rotary kiln causes environmental pollution due to the formation of Cr 6+ compounds. To meet the above challenge and operational demands due to increased use of alternative fuels, now-a-days iron-alumina or hercynite spinel is being used instead of chromite as chrome free material. Till date hercynite is rarely available in nature and electro-fusion is the main process of manufacturing hercynite in the industry. However, the main drawbacks of electrofusion process are time and energy consumption. This paper describes the synthesis of hercynite by plasma fusion, which is a new, faster and economic process, and also its refractory properties for application in cement rotary kiln. Bulk density of plasma fused hercynite is 3.86 g.cm –3 and thermal expansion at 1000°C is 0.85%. The developed magnesia hercynite brick shows higher performance and is also cost effective than the conventional magnesia chrome brick. GRAPHICAL ABSTRACT: